Integrative Multi‐Omics Mendelian Randomization Analysis Identifies NIT2 as a Potential Metabolic Risk Gene in Hepatocellular Carcinoma - Ziyue Liao; Qinghua Fang; Yue Chen; Xiangyu Yang; Haijuan Wu; Hongyang Wang; Jian Gao (The Journal of Gene Medicine, 2026)
ABSTRACT Background Metabolic pathways are crucial in hepatocellular carcinoma (HCC) pathogenesis, but causal metabolic genes remain unclear. This study used Summary data‐based Mendelian Randomization (SMR) and colocalization to identify metabolism‐related genetic loci influencing HCC risk. Methods Differentially expressed genes in hepatic malignancy phenotype versus normal tissues from TCGA and GTEx were analyzed. Metabolism‐related candidates were examined via SMR and colocalization using multi‐omics data: methylation (mQTL), expression (eQTL), and protein (pQTL) quantitative trait loci. Results Multi‐omics integration identified NIT2 as a key metabolic regulator for HCC. The cg13016775 locus of NIT2 was associated with elevated HCC risk at gene (OR = 1.618, 95% CI: 1.199–2.182) and protein (OR = 4.432, 95% CI: 1.783–11.018) levels. Colocalization supported a shared causal variant (PPH4 > 0.6), linking NIT2 to hepatocarcinogenesis via metabolic regulation. Conclusions This study provides multi‐omics evidence for NIT2 as a potential causal gene in HCC, enhancing understanding of metabolic contributions to HCC pathogenesis and highlighting integrative genomics for uncovering causal relationships.